Calcium-dependent activator protein for secretion 2 is involved in dopamine release in mouse midbrain neurons - Iguchi, Hirotoshi; Katsuzawa, Takumi; Saruta, Chihiro; Sadakata, Tetsushi; Kobayashi, Shota; Sato, Yumi; Sato, Akira; Sano, Yoshitake; Maezawa, So; Shinoda, Yo; Furuichi, Teiichi (Frontiers in Molecular Neuroscience, 2024)
The Ca2+-dependent activator protein for secretion (CAPS/CADPS) family protein facilitates catecholamine release through the dense-core vesicle exocytosis in model neuroendocrine cell lines. However, it remains unclear if it induces dopamine release in the central neurons. This study aimed to examine the expression and function of CADPS2, one of the two CADPS paralogs, in dopamine neurons of the mouse midbrain. This study shows that CADPS2 was expressed in tyrosine hydroxylase and the vesicular monoamine transporter 2 (VMAT2)-positive dopaminergic neurons of the midbrain samples and primary mesencephalic cell cultures. Subcellular fractions rich in dopamine were collected using immunoaffinity for CADPS2 from midbrain protein extracts. Cell imaging using fluorescent false neurotransmitter FFN511 as a substrate for VMAT2 showed decreased activity-dependent dopamine release in Cadps2-deficient cultures, compared to that in wild-type cultures. These results suggest that CADPS2 is involved in dopamine release from the central neurons, indicating its involvement in the central dopamine pathway.